2020
DOI: 10.1186/s13058-020-01340-4
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density change in a cohort of premenopausal women receiving tamoxifen for breast cancer prevention over 5 years

Abstract: Background A decrease in breast density due to tamoxifen preventive therapy might indicate greater benefit from the drug. It is not known whether mammographic density continues to decline after 1 year of therapy, or whether measures of breast density change are sufficiently stable for personalised recommendations. Methods Mammographic density was measured annually over up to 5 years in premenopausal women with no previous diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Lastly, this was a short-term longitudinal study with change in VASS as a biomarker endpoint. Prior studies have observed that mammographic breast density measurements approximately 1 year after tamoxifen initiation are generally representative of longer-term changes [31,32]. Future work is needed to evaluate the persistence of effects of UST sound speed declines on breast cancer outcomes to establish VASS as a clinically relevant biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, this was a short-term longitudinal study with change in VASS as a biomarker endpoint. Prior studies have observed that mammographic breast density measurements approximately 1 year after tamoxifen initiation are generally representative of longer-term changes [31,32]. Future work is needed to evaluate the persistence of effects of UST sound speed declines on breast cancer outcomes to establish VASS as a clinically relevant biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, younger high-risk women who may benefit from CESM screening are also a target population for prevention strategies. Mammographic VBD and measurements of fibroglandular volume have been demonstrated as useful markers of breast density change associated with interventions that include chemoprevention [ 46 , 47 , 48 ], oophorectomy [ 49 ], diet [ 50 ], and weight loss [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Dense breast tissue can obscure a tumor when examining a mammogram image because both appear white and therefore can lead to reduced mammographic sensitivity and an increased chance of being diagnosed as breast cancer between routine screening mammograms. 2 , 3 Although there have been investigations into the interactions of some drugs with breast density, 4 the density remains relatively nonmodifiable, unlike other risk factors, such as body mass index and alcohol consumption. 5 It is estimated that a quarter to half of the population of women who are of breast screening age (40-75 years) have heterogeneously and extremely dense breasts.…”
Section: Introductionmentioning
confidence: 99%